Broadband Two-Array Metasurface-Gridded MIMO Antenna with Dual-CP Bi-Directional Capabilities - Nathapat Supreeyatitikul; Khwanlada Kakhong; Pusit Prasong; Chuwong Phongcharoenpanich; Jessada Konpang (My University, 2025)
This study presents a novel two-array MTS-gridded MIMO antenna with dual circular polarization (CP) bidirectional capabilities for full-duplex communications. The proposed antenna consists of two mirrored clusters, each comprising a single-element antenna formed by a 3 × 4 MTS-gridded element array, a circular patch, and a ground plane. The antenna demonstrates a wide measured return loss bandwidth (RLBW) of 56.46% (5 – 8.67 GHz), axial ratio bandwidth (ARBW) of 18.15% (6.26 – 7.44 GHz), and strong isolation below –22 dB. Peak gains of 6.5 dBic and 6.55 dBic were observed at 6.6 GHz and 6.54 GHz for Ports 1 and 2, respectively. Furthermore, the low envelope correlation coefficient (< 0.005) and high diversity gain (> 9.985 dB) validate its effectiveness for multi-port applications. The bidirectional radiation pattern and dual circular polarization support simultaneous transmission and reception, making the design well-suited for full-duplex MIMO operation.
Keywords: Antenna Design and Analysis; Full-Duplex Wireless Communications; Advanced Antenna and Metasurface Technologies